Equilibrium dynamics under lump-sum taxation in an exchange economy with skewed endowments - Mikko Puhakka (Bank of Finland, 2004)
I explore the dynamics in overlapping generations models with pure exchange and lump-sum taxes, when the second period after tax endowment is negative, and contrast the characteristics of equilibria to those of models with positive after tax endowments. In particular, if the intertemporal elasticity of substitution is less than unity, there can be only a two cycle or stable (ie indeterminate) equilibria for certain parameter values.With this value for that elasticity chaos and a cycle of any order can occur in a model with regular endowments.In a sense the lump-sum taxation in this model operates as a stabilizing device.The precise stability condition holds with a small discount factor and in economies with relatively high taxes in the first period.If the intertemporal elasticity of substitution is greater than unity, the steady state equilibria are unstable, and thus determinate, as is the case with the regular model.
URN:NBN:fi:bof-20140807262
Keywords: E21; E32; 330; overlapping generations economy; saving; cycles; lump-sum taxation